Needs Analysis as a Foundation for Developing an ESD-Based Science E-Module to Cultivate Elementary School Students’ Moral Awareness of Environmental Sustainability - Ayu Prasetyaningrum; Winarno Winarno; Peduk Rintayati (Teknodika, 2025)
This study aims to analyze the needs of elementary school students in relation to the development of a Science e-module based on Education for Sustainable Development (ESD) in order to foster green moral awareness. The background of this research lies in the low level of students’ awareness of environmental issues and the importance of integrating sustainability values into the learning process, particularly in science education. The research employed a qualitative descriptive method. Data were collected through interviews, observations, and documentation involving fourth-grade teachers and students. The analysis revealed that students require learning media that are interactive, contextual, and capable of building both understanding and a caring attitude toward the environment. These findings serve as a crucial foundation for designing an ESD-based e-module that aligns with the characteristics and learning needs of elementary school students. The development of this ESD-based e-module is expected to provide a solution for enhancing students’ understanding of scientific concepts while simultaneously instilling sustainability values from an early age.